Skill requirements versus workplace characteristics : exploring the drivers of occupational gender segregation - Bajka, Scherwin M. [Verfasser]; Combet, Benita [Verfasser]; Emmenegger, Patrick [Verfasser]; Seufert, Sabine [Verfasser] (My University, 2025)
"What role do skill requirements play in gendered occupational preferences? Previous research has emphasized workplace characteristics such as salaries and family-friendly work hours. Less attention has been paid to skill requirements, even though they are an important part of job descriptions and serve as reference points for individuals’ assessment of their suitability for occupations. Using a choice experiment among Swiss adolescents who are in the process of choosing their vocational training occupation, this article demonstrates that women and men have surprisingly similar preferences for workplace characteristics. In contrast, skill requirements are better predictors of gender differences in occupational preferences. We find that technical skills are critical in explaining gendered occupational preferences, with occupations that rely more heavily on new technologies attracting fewer women. At the same time, both genders prefer occupations that emphasize social interactions, suggesting that the prominent ‘people’ versus ‘things’ distinction does not adequately capture gendered occupational preferences." (authors' abstract; BIBB-Doku)

Die Anforderungen an technische Fähigkeiten sind ein wesentlicher Grund dafür, dass junge Frauen technologieintensive Berufe meiden. Das zeigt ein Experiment mit über 2'000 Jugendlichen, durchgeführt von Forschenden der Universität Bern und der Universität St. Gallen. Die Ergebnisse liefern neue Erklärungsansätze für die Geschlechterungleichheit auf dem Schweizer Arbeitsmarkt. […] Mittels eines Choice-Experiments untersuchte ein Team von Forschenden, von welchen Faktoren sich Jugendliche in der achten Klasse kurz vor ihrer Lehrstellenwahl besonders beeinflussen lassen. Die Resultate zeigen, dass junge Frauen und Männern bei zentralen Arbeitsplatzmerkmalen wie Gehalt, Teilzeitoptionen oder gesellschaftlicher Relevanz ähnliche Vorlieben haben. Deutlich werden die Unterschiede jedoch dort, wo es um die im Beruf geforderten Fähigkeiten geht: Junge Frauen zeigen eine klare Abneigung gegen technische Fähigkeiten, während junge Männer diese wertschätzen. (BIBB-Doku)
Keywords: P 1.1 Jugendliche; L 5 Beratung & Orientierung; 370; Jugendlicher; Berufswahl; Qualifikationsanforderung; Neue Technologien; Technikakzeptanz; Geschlechtsspezifische Faktoren; Schweiz